The Influence of Work Environment and Work Motivation Work on Employee Performance PT. Oasis Waters International - M Ronal Priandi; Roswaty Roswaty2; M. Bahrul Ulum (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to determine the application of work environment and work motivation and to determine the effect of work environment and work motivation on employee performance at PT. Oasis Waters International. This type of research is a descriptive quantitative method. Primary data collection using the method of observation and distribution of questionnaires. Secondary data were obtained from sample research techniques, documents, journals, and books related to the problems studied. The research sample is the employees of PT. Waters International totaling 54 employees. This study uses simple linear regression analysis and uses the SPSS Version 26.0 program. The results of this study indicate that the work environment and work motivation at PT. Oasis Waters International has done well. The results obtained from the significant test of work environment and work motivation variables on employee performance are 0.000 <0.05, meaning that partially work environment and work motivation have a positive effect on employee performance. From the coefficient test (R2) it is obtained for 0.385, this means that employee performance is influenced by the work environment and work motivation of 0.802.